Meyd un kale, froy un vayb : the characterisation of the feminine in early eighteenth century Yiddish chapbooks - Dowling, JL (1996)
This thesis is concerned with the behaviour of female characters in four, popular, non-ritualistic Yiddish chapbooks published at the beginning of the eighteenth century: Mayse fun a kale, Mageleyne lid, Mayse man un vayb, and Mayse fun Shloyme hameylekh. Most Yiddish chapbooks from this time do not narrate stories which include women as the main protagonists. However, these four rhymed booklets, published before the influence of either the Enlightenment and Hasidism, do include women as principal characters. The mimetic qualities of these four chapbooks, although obviously distorted in that they are presented from a highly educated male viewpoint, demonstrate a clear perspective on how women should behave, especially those whom the author could reach through his didactic, yet entertaining material. Through an analysis of the four booklets in question, one is able to derive a picture of how women were perceived in early modern Ashkenaz. It is also possible to draw a much smoother line of influence in the characterisation of the feminine from pre-modern Yiddish literature to modern Yiddish than drawn before now. Three specific questions are addressed in the thesis. The first of these concerns the dynamics in the relationships between men and women. How are relationships defined and prescribed? In light of this male/female dynamic, what is the relationship between gender and power? Finally, what is the cultural construction of gender, the prescriptions for proper behaviour, and how are women portrayed in chapbook literature? Keeping in mind that the mimetic quality of these fictive texts is a reflection of the attitudes of the author, it is the goal here to find the symbolic categories as they are defined in these four texts, and determine their meaning within the context of eighteenth century Ashkenaz. The thesis is presented in three parts. The first part presents introductory matters concerning terminology and orientations presented in the work. It also includes a background survey of the educational possibilities and limitations afforded women prior to the Haskole. The second part of the thesis details the characterisation of the feminine as presented in the texts, followed by the conclusions. Lastly, the texts themselves are presented in three formats: first, a scanned copy — with the discolourations and aging from the title page removed for demonstrative purposes — showing the original typefaces, decoration and publishing quality; the text is then presented in a more modern typeface, retaining however, original spellings; and lastly a translation of each text is included.